Realizing Fair and Sustainable National Sports Governance: Perspectives of Legal Protection and State Administration - Imelda, Chitra; Hasanuddin, Hasanuddin; Waliadin, Waliadin; Sangkut, M.; Novianti, Liza (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
National sports governance is a key element in the development of globally competitive human resources. Sport not only serves as physical development, but also as a means of strengthening the values of togetherness and justice. Based on Law Number 11 of 2022 and various related regulations, this governance system emphasizes legal protection for athletes, coaches and support personnel through fair employment contracts and social security. However, implementation challenges, such as budget constraints, human resource competencies, and supervision, hinder the effectiveness of the policy. Synergy between a comprehensive legal framework and adaptive public administration is needed to create an inclusive, sustainable and competitive sport system.